Effectiveness of VA-ECMO plus intra-aortic balloon pump for cardiac shock in patients with type A aortic dissection: a case series - Hui Wu; Pengfei Chen; Jinhua Wei; Fengbo Pei; Mingjian Chen; Diming Zhao; Liqing Wang; Jundong Pu; Zujun Chen (Journal of Cardiothoracic Surgery, 2023)
Abstract Limited reports exist on the utilization of venoarterial extracorporeal membrane oxygenation (VA-ECMO) following aortic dissection surgery, possibly due to concerns regarding complications. This case series aimed to evaluate the effectiveness and safety of using VA-ECMO in combination with intra-aortic balloon pump (IABP) for managing postoperative cardiogenic shock in patients with type A aortic dissection (AAD). The study included nine patients with an average age of 57.0 ± 9.5 years. The patients underwent various surgical procedures, including coronary artery bypass grafting (CABG) and aortic root reconstruction. The results showed that the combined use of VA-ECMO and IABP was feasible and effective in managing postoperative cardiogenic shock in AAD patients. However, the in-hospital mortality rate was high, with six out of nine patients succumbing to the condition. Among the patients who received VA-ECMO plus IABP in the operating room, four were successfully weaned from VA-ECMO, and three survived with a mean follow-up of 20 months. The study also highlighted the potential risks of renal complications associated with VA-ECMO and IABP. The findings suggest that the combined therapy of VA-ECMO and IABP may be beneficial for patients who have difficulty weaning from cardiopulmonary bypass (CPB) after AAD surgery.